(untitled) (Journal of the College of Basic Education, 2023)
In this research, the reliability function was estimated for the exponential distribution with two parameters by the standard Bayesian method, as well as the estimation of the parameters of this distribution, i.e. the measurement parameter and the displacement parameter, i.e. the reliability that starts from a certain time and not from zero, and when compensating for the space of the displacement parameter when it is zero, it is neglected because this time The rhombus represents the warranty period.